2009 IEEE International Conference on Communications Workshops 2009
DOI: 10.1109/iccw.2009.5208046
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study of a New Green BitTorrent

Abstract: Abstract-The use of P2P technologies, such as BitTorrent, to distribute legal content to consumers is actively being explored as a means of reducing both file download times and the energy consumption of data centers. This approach pushes the energy use out of the data centers and into the homes of content consumers (who are also then content distributors). The current BitTorrent protocol requires that clients must be fully poweredon to be participating members in a swarm. In this paper, we show that simple ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 6 publications
(6 reference statements)
0
31
0
Order By: Relevance
“…For example, routing algorithms [Chabarek et al 2008;Restrepo et al 2009;] and network protocols Blackburn and Christensen 2009] can be improved to save energy.…”
Section: Coordination and Network Wide Solutionsmentioning
confidence: 99%
“…For example, routing algorithms [Chabarek et al 2008;Restrepo et al 2009;] and network protocols Blackburn and Christensen 2009] can be improved to save energy.…”
Section: Coordination and Network Wide Solutionsmentioning
confidence: 99%
“…It has been shown that Green BitTorrent can save about 25% of the energy, in comparison with legacy BitTorrent [18]. The drawback consists in an increased average download time experienced by peers which is, however, acceptable.…”
Section: Energy Efficiency In Bittorrentmentioning
confidence: 92%
“…This approach is exploited in Green BitTorrent, proposed in [18]. Green BitTorrent is an extended version of BitTorrent for energy efficiency and • Connected.…”
Section: Energy Efficiency In Bittorrentmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, energy-efficient BitTorrent proposals have been studied in [10] and [11]. Blackburn et al [10] designed and implemented a green BitTorrent client that can drop its connections and go to sleep, yet still be active as a swarm member. This work is the first version to specifically look at the BitTorrent protocol in terms of energy savings.…”
Section: Related Workmentioning
confidence: 99%